Evaluating the performance of indian banking sector using DEA during post-reform and global financial crisis - Kumar, Mukesh; Charles, Vincent; Sekhar Mishra, Chandra (Journal of Business Economics and Management, 2016)
The purpose of the study is to examine the performance of Indian banking sector in terms of efficiency, returns to scale, and total factor productivity change. The technique of data envelopment analysis is applied due to its flexibility to incorporate multiple inputs and multiple outputs without any underlying assumption on the functional form. There is growing tendency of public sector banks operating under increasing returns to scale, implying that substantial gains could be obtained from altering scale via either internal growth or consolidation in the sector. In terms of productivity, the results show a positive change in both the sectors due to technological change, possibly as a result of adoption of latest technology and new business practices in post reform period. However, there is an evidence of shrink in the market and negative growth in productivity in both the sectors during the period of global financial crisis. The main contribution of the paper is to empirically provide the evidences to resolve the debate if the global financial crisis had any impact on the performance of banking sector in India.